2021
DOI: 10.5603/ep.a2021.0072
|View full text |Cite
|
Sign up to set email alerts
|

Copeptin as a novel biomarker of cardiometabolic syndrome

Abstract: This article has been peer reviewed and published immediately upon acceptance.It is an open access article, which means that it can be downloaded, printed, and distributed freely, provided the work is properly cited. Articles in "Endokrynologia Polska" are listed in PubMed. The final version may contain major or minor changes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Several studies indicated that AVP contributes to the development and progression of diabetic microangiopathy and serum copeptin may serve as an independent marker of renal, heart or retinal microcirculation involvement in type 2 diabetes patients. 38 In our SSc group, higher concentrations of serum copeptin were observed in patients presenting "late" NVC pattern, which is characterized by irregular enlargement of the capillaries, few or absent giant capillaries and haemorrhages, ramified and bushy capillaries and progressive capillary loss (50-70%) with formation of extensive avascular areas (vascular desertification). These alterations, namely abnormal vessel morphology, changes in capillary number and disorganization of microcirculation architecture observed in the "late" NVC pattern stem from insufficient angio-and vasculogenesis.…”
Section: Discussionmentioning
confidence: 60%
See 2 more Smart Citations
“…Several studies indicated that AVP contributes to the development and progression of diabetic microangiopathy and serum copeptin may serve as an independent marker of renal, heart or retinal microcirculation involvement in type 2 diabetes patients. 38 In our SSc group, higher concentrations of serum copeptin were observed in patients presenting "late" NVC pattern, which is characterized by irregular enlargement of the capillaries, few or absent giant capillaries and haemorrhages, ramified and bushy capillaries and progressive capillary loss (50-70%) with formation of extensive avascular areas (vascular desertification). These alterations, namely abnormal vessel morphology, changes in capillary number and disorganization of microcirculation architecture observed in the "late" NVC pattern stem from insufficient angio-and vasculogenesis.…”
Section: Discussionmentioning
confidence: 60%
“…Several studies indicated that AVP contributes to the development and progression of diabetic microangiopathy and serum copeptin may serve as an independent marker of renal, heart or retinal microcirculation involvement in type 2 diabetes patients. 38 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADH has a very short half-life and is difficult to measure. Copeptin, which is found at the C-terminus of anti-diuretic hormone prodrugs, is the most commonly used marker for detecting plasma ADH ( Christ-Crain, 2019 ; Kim et al, 2021 ; Szmygin et al, 2021 ). The results of this study revealed that the morphological changes of the hypothalamic were obvious, and the expression of copeptin, ADH mRNA, and AQP 2 was increased in the model group rats, indicating that oliguria in acute alcoholism was caused by excessive secretion of ADH from hypothalamic tissues to promote water reabsorption by the kidney.…”
Section: Discussionmentioning
confidence: 99%
“…However, as a small peptide of nine amino acids, the blood level of AVP is difficult to quantitatively analyze due to its short half-life[ 10 ]. Copeptin is a 39-amino-acid glycopeptide which contains the C-terminus of AVP precursor, making it an effective surrogate marker for AVP release[ 11 , 12 ]. As a result of osmotic stress and osmotic stimulation, a high level of copeptin has been demonstrated in patients with ACLD[ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%